Feasibility and acceptability of my electronic personal health record monitor (MY-EPHRM) - Lua Pei, Lin; Umar Idris, Ibrahim (International Journal of Pharmacy and Pharmaceutical Science, 2015)
Objectives: Smartphones could be used as a novel approach to improve medication adherence and patient’s behaviour; due to constant accessibility, and the provision of a repository for health and medication information. This study aimed to assess the feasibility and acceptability of the use of My Electronic Personal Health Record Monitor (My-ePHRM), a newly-developed application (software) for personal health record monitoring as well as the factors that predict its acceptability.